MANAJEMEN LABA: TATA KELOLA PERUSAHAAN DAN ALIRAN KAS BEBAS - ARYA PRADIPTA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this study is to examine the factors that influence earnings management in Indonesia. Those factors are profitability, leverage, firm size, audit committee, independent commissioner proportion, institutional ownership, managerial ownership and free cash flow. The population are non financial companies listed in Indonesia stock exchange. This study used 283 samples and samples selection procedure used purposive sampling. This research uses multiple regression analysis method. The result of this study shows that profitability and free cash flow have influence to earnings management. While, leverage, firm size, audit committee, independent commissioner proportion, institutional ownership and managerial ownership do not have influence to earnings management.